Micro anatomical studies of the conducting system in the heart of the pig - SATHYMORRTHY, O R; RAMESH, GEETHA (The Indian Journal of Animal Sciences, 2011)
The heart from pigs at different ages, viz. day-old, 1 month, 3 month, 6 month, one-and-half year, 2-year, 3-year and 4-year were utilized for this study. The conduction system of the heart consisted of sinuatrial node, atrioventricular node and atrioventricular bundle. The sinuatrial node was situated in the region of sulcus term inalis, right to the junction of anterior vena cava with the right atrium. The atrioventricular node was located at the lower position within the septal wall of the light atriun1 below the coronary sinus. The atrioventIicular bundle arose from the AV - node, perforated the fibrous ring and reached the interventricular septum at its apex where the insertion of the cuspis septalis of the right ventricle was noticed. Histologically, the sinuatrial node was a much loose structure with more fibrous and vascular connective tissue. Nerve bundles and ganglion cells were noticed at the periphery of the node. The AV-node possessed a con1pact nodal region and an extensive transitional nodal region. The penetrating AV-bundle coursed down the interventricular septum and divided into right and left bundle branches. Â